VEGETABLE MARKET AT THE PRESENT STAGE: NEW CHALLENGES - DUKHNYTSKYI, Bogdan (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article considers current aspects of functioning the vegetable market of Ukraine, including detailing the assortment and regional structure of production. Its dynamics is clearly divided into periods up to and including 2021 as well as beyond after. The balance of vegetable crops according to the main spheres of their utilization is presented. Their use for food needs is observed, depending on the volume of production and without a particular influence of export and import. The changes that took place in foreign trade in vegetables and contributed to the increase of its negative balance are highlighted. It was a complex of reasons with a permanent and temporary nature, which gradually formed a different market situation. The impact of the war and its consequences on the vegetable sector of our country was separately investigated. Attention was paid to the sharp decrease in production, the increase in prices, the relocation of existing industry enterprises and the emergence of new ones. The critical importance of the southern regions for the food supply of vegetable crops in the open soil and greenhouses for the entire Ukraine has been statistically proven. The positions related to tomatoes, sweet peppers, eggplants, and melon crops became the most vulnerable. The new trends of the market, mainly forced, which are observed during 2022-2023 and will influence its development in the near future, are characterized. Even taking into account the large number of refugees and displaced persons, the needs of our domestic market are not fully satisfied, there remains a high impact of the seasonal factor. High unpredictability and significant risks to the industry due to the impact of the war were noted. However, Ukrainian manufacturers and other market participants should still develop domestic and international activities.
Keywords: vegetables; challenges; war; transformation; population; prospects